2022
DOI: 10.1111/pan.14425
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetic modeling and simulation to understand diamorphine dose‐response in neonates, children, and adolescents

Abstract: Pharmacokinetic-pharmacodynamic modeling and simulation can facilitate understanding and prediction of exposure-response relationships in children with acute or chronic pain. The pharmacokinetics of diamorphine (diacetylmorphine, heroin), a strong opioid, remain poorly quantified in children and dose is often guided by clinical acumen. This tutorial demonstrates how a model to describe intranasal and intravenous diamorphine pharmacokinetics can be fashioned from a model for diamorphine disposition in adults an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…These profiles ( Figure 5 ) described intravenous and intranasal dosing regimens. These indicated that morphine exposure in children after intranasal diamorphine 0.1 mg/kg was similar to after intranasal diamorphine 5 mg in adults [ 120 ].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…These profiles ( Figure 5 ) described intravenous and intranasal dosing regimens. These indicated that morphine exposure in children after intranasal diamorphine 0.1 mg/kg was similar to after intranasal diamorphine 5 mg in adults [ 120 ].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Drug PK parameters can then be simulated to determine optimal dosing regimens for specific populations. [6][7][8][9] A major barrier to designing PKPD studies in children is the lack of PD scoring systems to help delineate the target effect. In this review we will discuss PKPD modeling in analgo-sedation, with a particular focus on PD endpoints and the difficulties associated with these measures in children.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop these models, the target‐concentration effect relationship needs to be well‐defined in order to determine a target concentration associated with a target effect. Drug PK parameters can then be simulated to determine optimal dosing regimens for specific populations 6–9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to measure total plasma concentrations in infants undergoing lower abdominal surgery and combine this with data from other levobupivacaine studies to generate a neuraxial pharmacokinetic model which could then be used to predict levobupivacaine plasma concentrations at variable intervals after the initial caudal in neonates infants and older children. 5,6 2 | ME THODS…”
Section: Introductionmentioning
confidence: 99%